Pengembangan E-Modul Pembelajaran Berbantuan Flip PDF pada Mata Pelajaran IPAS Materi Bagaimana Wujud Benda Berubah di Kelas IV SDN 03 Pontianak Selatan - Hanim Mufidah; Hamdani Hamdani; Rio Pranata (Departement of Mathematics Education, 2024)
This development research aims to produce a Flip PDF-assisted learning e-module product for the science and science subject material on how the shape of objects changes in class IV SDN 03 South Pontianak that is valid and feasible. The method applied is research and development (R&D) using the ADDIE model. Quantitative data was obtained from the results of product evaluations from validators and the results of students filling out feasibility questionnaires for learning e-modules assisted by flip PDF. Qualitative data was obtained from suggestions from validators, teachers and students. The research instrument was in the form of a questionnaire. Results based on the level of validation of the PDF flip-assisted learning e-module in the science and sciences subject material on how the shape of objects changes in class IV SDN 03 South Pontianak based on the material aspect obtained an average of 4.85 with the category